Prognostic Value of Changes in Preoperative and Postoperative Serum CA19-9 Levels in Gastric Cancer - Song, Xiao-Hai; Liu, Kai; Yang, Shi-Jie; Zhang, Wei-Han; Chen, Xiao-Long; Zhao, Lin-Yong; Chen, Xin-Zu; Yang, Kun; Zhou, Zong-Guang; Hu, Jian-Kun (Frontiers in Oncology, 2020)
Objective: The prognostic signiﬁcance of serum CA19-9 levels in gastric cancer patients remains a matter debate. The aim of this study was to determine the prognostic value of changes in preoperative and postoperative serum CA19-9 levels in patients with gastric cancer. Methods: A total of 1046 gastric cancer patients who underwent curative gastrectomy in West China Hospital of Sichuan University from January 2011 to December 2016 were analyzed retrospectively. Patients were categorized by minimum P-value using X-tile, while the baseline confounders for CA19-9 changes were balanced through propensity score matching (PSM). The relationships between CA19-9 changes and other clinicopathologic features were measured. Univariate and multivariate analysis were performed to explore the risk factors associated with survival outcomes. Results: We included 653 patients. Changes in CA19-9 levels significantly correlated with age, tumor size, macroscopic type, histological grade, T stage and TNM stage. Kaplan–Meier curves revealed that patients with CA19-9 changes less than 20% had significant better overall survival than those with changes more than 20% (p <0.001); Cox regression analysis revealed the CA19-9 change (p = 0.010), gender (p = 0.031), histological grade (p = 0.036) and TNM stage (p <0.001) were independent risk factors for survival after PSM. Stratification analysis indicated that patients with CA19-9 change more than 20% had worse prognosis that those with CA19-9 change no more than 20% in male (p=0.002), poorly differentiated or undifferentiated type (p=0.031) and TNM stage III (p=0.006). Conclusion: Changes in preoperative and postoperative serum CA19-9 levels were closely associated with clinicopathological traits and was an independent prognostic factor in gastric cancer patients. This parameter may be a reliable marker for prediction of survival.